2016
DOI: 10.1074/jbc.m116.723064
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Attributes of the Interleukin-36 Receptor

Abstract: Signal transduction by the IL-36 receptor (IL-36R) is linked to several human diseases. However, the structure and function of the IL-36R is not well understood. A molecular model of the IL-36R complex was generated and a cell-based reporter assay was established to assess the signal transduction of recombinant subunits of the IL-36R. Mutational analyses and functional assays have identified residues of the receptor subunit IL-1Rrp2 needed for cytokine recognition, stable protein expression, disulfide bond for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 30 publications
(36 reference statements)
0
61
0
Order By: Relevance
“…It has also been demonstrated that disulfide bonds and N‐linked glycosylation in the ectodomain of IL‐36R could affect signaling transduction by regulating protein accumulation and IL‐36R trafficking to the cell surface, respectively. In addition, a single nucleotide gene polymorphism for IL36R , A471T, resulting in a substitution in the TIR domain leads in decreased IL‐36R signaling by reducing the interaction with IL‐1RAcP …”
Section: Il‐36 Expression and Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that disulfide bonds and N‐linked glycosylation in the ectodomain of IL‐36R could affect signaling transduction by regulating protein accumulation and IL‐36R trafficking to the cell surface, respectively. In addition, a single nucleotide gene polymorphism for IL36R , A471T, resulting in a substitution in the TIR domain leads in decreased IL‐36R signaling by reducing the interaction with IL‐1RAcP …”
Section: Il‐36 Expression and Biochemistrymentioning
confidence: 99%
“…In addition, a single nucleotide gene polymorphism for IL36R, A471T, resulting in a substitution in the TIR domain leads in decreased IL-36R signaling by reducing the interaction with IL-1RAcP. 9 The IL-36 cytokines are located within the same gene cluster on human chromosome 2 as the genes for all other IL-1 family cytokines except for IL-18 and IL-33. The IL-36R also lies in the IL-1R family locus on human chromosome 2.…”
mentioning
confidence: 99%
“…Each half of the heterodimer is showing up as single band with a molecular mass of ϳ70 kDa, which is higher than theoretical molecular mass of 63 kDa. Receptors showing higher molecular mass by SDS-PAGE are likely due to glycosylation (12).…”
Section: Figure 2 Sds-page Gels Showing Purified Soluble Forms Of Rementioning
confidence: 99%
“…However, some attempts to measure the first event of IL-36 activation, which is the direct binding of cytokines and IL-36R, have not been successful (1). Furthermore, a recent study shows IL-36R interacts with IL-1RAcP even in the absence of the agonist (12). Knowledge of how IL-36R becomes activated and inhibited is important to understand a potential drug target that has implications in multiple inflammatory diseases including psoriasis.…”
mentioning
confidence: 99%
“…HEK293T cells lack IL-1Rrp2, but expresses IL-1RAcp. Transient transfection with a plasmid to express IL-1Rrp2 and reconstitute IL-36R signaling in HEK293T cells [29]. Overexpression of RNF125 in HEK293T cells was found to increase the level of polyubiquitinated IL-1Rrp2 only when the cells were induced with IL-36γ, mimicking the property observed in NCI cells that express endogenous IL-36R (Fig.…”
Section: Recombinant Rnf125 Ubiquitinates Il-1rrp2 In Hek293t Cellsmentioning
confidence: 99%